Photoexcitation of the blue light using FAD photoreceptor AppA results in ultrafast changes to the protein matrix - Lukacs, Andras; Haigney, Allison; Brust, Richard; Zhao, Rui-Kun; Stelling, Allison L; Clark, Ian P; Towrie, Michael; Greetham, Gregory M; Meech, Stephen R; Tonge, Peter J (Journal of the American Chemical Society, 2011)
Photoexcitation of the flavin chromophore in the BLUF photosensor AppA results in a conformational change that leads to photosensor activation. This conformational change is mediated by a hydrogen-bonding network that surrounds the flavin, and photoexcitation is known to result in changes in the network that include a strengthening of hydrogen bonding to the flavin C4═O carbonyl group. Q63 is a key residue in the hydrogen-bonding network, and replacement of this residue with a glutamate results in a photoinactive mutant. While the ultrafast time-resolved infrared (TRIR) spectrum of Q63E AppA(BLUF) is characterized by flavin carbonyl modes at 1680 and 1650 cm(-1), which are similar in frequency to the analogous modes from the light activated state of the wild-type protein, a band is also observed in the TRIR spectrum at 1724 cm(-1) that is unambiguously assigned to the Q63E carboxylic acid based on U-(13)C labeling of the protein. Light absorption instantaneously (<100 fs) bleaches the 1724 cm(-1) band leading to a transient absorption at 1707 cm(-1). Because Q63E is not part of the isoalloxazine electronic transition, the shift in frequency must arise from a sub picosecond perturbation to the flavin binding pocket. The light-induced change in the frequency of the Q63E side chain is assigned to an increase in hydrogen-bond strength of 3 kcal mol(-1) caused by electronic reorganization of the isoalloxazine ring in the excited state, providing direct evidence that the protein matrix of AppA responds instantaneously to changes in the electronic structure of the chromophore and supporting a model for photoactivation of the wild-type protein that involves initial tautomerization of the Q63 side chain.